Penerapan Model Pembelajaran Mind Mapping untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Al-Qur’an Hadits Kelas VII di MTs Negeri 1 Pekalongan - Athik Dina Nasichah; Kartika Sulistioningrum; Fika Khabibati (Al-Nizam: Indonesian Journal of Research and Community Service, 2024)
Abstract: This study aims to describe the application of the Mind Mapping learning model in improving student learning outcomes in the subject of Al-Qur'an Hadith class VII at MTs Negeri 1 Pekalongan. The approach used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The subjects of the study consisted of Al-Qur'an Hadith subject teachers and class VII students at MTs Negeri 1 Pekalongan. The discussion in this study includes the application of the Mind Mapping model in the context of learning Al-Qur'an Hadith, supporting and inhibiting factors during the application process, and the impact of the application of the model on student learning outcomes. The results of the study indicate that Mind Mapping is effective in helping students understand and remember Al-Qur'an Hadith material visually and in a structured manner. Supporting factors for the success of this model include active teacher involvement, availability of learning media, and student enthusiasm. The obstacles include limited time and students' ability to compile concept maps. Overall, the Mind Mapping learning model makes a positive contribution to improving the quality of learning and student learning outcomes. Keywords: Mind Mapping, Al-Qur'an Hadith Learning Outcomes